Phycomediation of cadmium contaminated aqueous solutions using Chlamydomonas sp.: process optimization and adsorption characterization - Alharbi, Reem Mohammed; Abdel-Raouf, Neveen; Mohamed, Mostafa Shaaban; Fathy, Wael A.; Ibraheem, Ibraheem Borie M.; Hozayen, Walaa Gamal (Frontiers in Bioengineering and Biotechnology, 2025)
The contamination resulting from heavy metals present in industrial effluents represents a critical global challenge, posing profound risks to aquatic ecosystems and human health. Industrial activities worldwide release wastewater laden with toxic metals, prominently cadmium (Cd), into rivers, lakes, and oceans, frequently surpassing permissible limits. Current treatment technologies are costly and may produce secondary pollutants, thereby necessitating the urgent development of sustainable and cost-effective alternatives. This study investigates the efficacy of the microalga Chlamydomonas sp. as a natural biosorbent for the phycoremediation of cadmium from industrial effluent. Critical parameters affecting cadmium biosorption, including pH, contact time, Cd concentration, and biomass dosage, were optimized. Under optimal conditions of 25°C, pH 4, Cd concentration of 50 mg/L, a contact time of 60 min, and a biomass dosage of 0.8 g/L, Chlamydomonas demonstrated a cadmium adsorption capacity of 44.75 mg/g, achieving a removal efficiency of 95.6%. Analytical techniques such as SEM, XRD, FTIR, DLS, and zeta potential analysis confirmed cadmium binding to the algal biomass. Kinetic modeling suggested a pseudo-second-order process, while isotherm analysis adhered to the Langmuir model, indicating considerable adsorption capacity and efficiency under optimal conditions. These results support using Chlamydomonas as an effective biosorbent for integration into global industrial wastewater treatment systems. This biological approach offers a sustainable and cost-efficient method for heavy metal removal, reducing secondary pollution and aligning with international efforts to mitigate water contamination. Implementing bioremediation strategies could greatly decrease the release of toxic metals into aquatic ecosystems, providing a scalable and environmentally friendly solution for industrial applications globally.